The architectural ensemble of the scientific institutes in Pushchino: history and design principles in the 1950s–1980s - Antipin Konstantin S. (Архитектон, 2024)
The study covers the period from the beginning of designing the scientific research town of Pushchino in the Moscow region in 1956 to the end of its active construction in the late 1980s. The focus is on the analysis of the solutions for the area of scientific research institutes in the planning projects of different years collected as a result of archival research. Changes in the design approaches are identified and examined in the context of both the general course of development of Soviet architecture and the specific techniques of scientific research building design. Such techniques were developed and implemented by the same institute that carried out the design of Pushchino. Stages in the design of the scientific research town are identified. The contribution at each historical stage to the architectural ensemble of the scientific institutes, which had formed by the late 1980s and still exists today, is determined. Examining the projects of Pushchino in the context of other academic towns enriches the understanding of not only the history of this specific ensemble but also of how all the scientific complexes of the USSR were designed during the period under study. Drawing parallels between various projects makes it possible to gain a deeper understanding and identify common principles underlying their development.